Topography as a determinant of range extent and overlap : a species level phylogenetic reconstruction and geographical range analysis of Syncarpha (Asteraceae) - Haiden, Sarah (Department of Biological Sciences, 2017)
Understanding what determines species' geographic range extents has several implications for questions in ecology, evolution and conservation biology. The Cape Floristic Region of South Africa is noted for its remarkably high geographic species turnover, often attributed to the exceptional environmental heterogeneity of the region. The complex and highly dissected topography of the CFR provides a model environment in which to investigate the relationship between altitude and species range extent, as well as explore the role of topography in speciation and current range overlap. I examined these questions in the context of Syncarpha, a genus within the Asteraceae tribe Gnaphalieae (paper daisies). A Bayesian analysis of combined plastid and nuclear genes provided the robust, dated phylogenetic hypothesis required to assess the monophyly of the genus, as well as reconstruct the signal of geographic speciation within the lineage. The phylogeny recovered Syncarpha as polyphyletic, comprising two clades with good support, placing the small CFR-endemic genus Edmondia as sister to the larger Syncarpha clade. Using realised range extent estimates and modelled potential distributions of Syncarpha and Edmondia species, this study confirms the importance of topography as a factor constraining species' distributions, and thereby enhancing the scope for their allopatric isolation. The relationship between altitude and realised range extent was found to be unimodal, with ranges being restricted at both high- and low-altitudes, and more extensive at intermediate altitudes. Range filling (the ratio between realised and potential range extent) was also lower in high- and low-altitude taxa compared to mid-altitude taxa. Dispersal limitation, owing to the insular nature of montane habitats, seems the most likely mechanism to restrict the ranges of high-altitude taxa, whereas edaphic factors are more likely responsible for the restricted ranges of low-altitude taxa. Furthermore, age-range correlations confirm the role of altitude in maintaining a stronger signal of allopatry among recently diverged clades, where montane clades present lower levels of range overlap than those at intermediate altitudes. Thus, the role of topography in limiting dispersal, and hence constraining species distributions, has consequences for understanding the historical diversification of a lineage, as well as implications for management practices in light of climate change-induced range shifts.